BIODIVERSITASSERANGGA DI PERKEBUNAN KAKAO UNTUK PENGELOLAAN PENYAKIT BUSUK BUAH (PBK) - Ni Gusti Agung Gde Eka Martiningsih; Cokorda Javandira; I Made Suryana; Anugrah Mahima (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Cocoa is one of the export commodities from the plantation subsector which is a national superior commodity, Cocoa is one of the export commodities from the plantation subsector which is a national superior commodity. Cocoa development in Indonesia is inseparable from a variety of problems encountered from the upstream to downstream sectors. Some problems in the upstream sector include plant productivity is still low, as well as the presence of pests and diseases. Species diversity can be used to express community structures. Measures of diversity and their causes cover most of the thoughts about ecology. In biodiversity it always includes ecosystems, species diversity and genetics. In biodiversity, the diversity of insect species is included. Insects are a group of dominant organisms in the biosphere in the form of land. In terms of quantity, the existence of insects is vital to maintaining the balance of natural ecosystems. This is mainly because diversity can produce stability and thus relate to cocoa development centers in Tabanan. The purpose of this study is 1). Knowing insect and weed biodiversity in Cocoa plantations in the Old Marga Tabanan Village 2) Mapping the Agroecosystem in Cocoa plantations to support the sustainability of cocoa cultivation in the Old Marga Tabanan village. This research is expected to find the condition of the cocoa plantation biodiversity in developing various biophysical, social and economic aspects in Tabanan Regency. Important contributions can be given, namely: (a) Results of biodiversity studies on cocoa plantations, (b) Increased understanding of cocoa plantation ecosystems and (c) Improving environmental conditions and improving cocoa production.